[Turning off the red light ; Taong grasa ; National treasure Levy Celerio [videorecording] - Lazaro, Cheche (The Probe Team, 1992)
Tackles the issues on the clean-up drive of Manila Mayor closure of clubs, bars and trading in Ermita transferring it into a morally safe "tourist place." Takes a look at the lives of psychotic and mentally imbalanced street vagrants. An interview of Levy Celerio who has written for and composed over 4,000 Filipino songs that have lived for generations.